2016
DOI: 10.1016/j.oceaneng.2015.10.048
|View full text |Cite
|
Sign up to set email alerts
|

A risk assessment approach to improve the resilience of a seaport system using Bayesian networks

Abstract: Over the years, many efforts have been focused on developing methods to design seaport systems, yet disruption still occur because of various human, technical and random natural events. Much of the available data to design these systems are highly uncertain and difficult to obtain due to the number of events with vague and imprecise parameters that need to be modelled. A systematic approach that handles both quantitative and qualitative data, as well as means of updating existing information when new knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(65 citation statements)
references
References 23 publications
0
63
0
2
Order By: Relevance
“…The use of BNs is spreading to almost all areas: safety and reliability modeling, operational risk in finance, information retrieval, environment, medicine or, according to (Fenton & Neil, 2013) dependability, risk analysis and maintenance as well as to architecture design developing models to capture change impact analysis (Tang et al, 2007), data mining, determining and explicitly displaying the relationship among variables, representing expert knowledge and combining expert knowledge and empirical data, and identifying key uncertainties (Marcot & Penman, 2019). In addition to the previously mentioned, Bayesian Belief networks also have a variety of applications in the following fields:…”
Section: Application Of Bbnsmentioning
confidence: 99%
“…The use of BNs is spreading to almost all areas: safety and reliability modeling, operational risk in finance, information retrieval, environment, medicine or, according to (Fenton & Neil, 2013) dependability, risk analysis and maintenance as well as to architecture design developing models to capture change impact analysis (Tang et al, 2007), data mining, determining and explicitly displaying the relationship among variables, representing expert knowledge and combining expert knowledge and empirical data, and identifying key uncertainties (Marcot & Penman, 2019). In addition to the previously mentioned, Bayesian Belief networks also have a variety of applications in the following fields:…”
Section: Application Of Bbnsmentioning
confidence: 99%
“…Resilience is strongly linked to the concept of the progression of unknown transitional states not foreseen by the system. Up to now, few works have focused on taking imperfections into account in resilience management (Hosseini, Al Khaled, & Sarder, ; John, Yang, Riahi, & Wang, ; Mojtahedi, Newton, & Von Mading, ; Nogal, O'Connor, Martinez‐Pastor, & Caufiled, ; Yodo, Wang, & Zhou, ). Appropriate models should be proposed to represent imperfection with a twofold constraint: adaptation to the type of data (elicitation of expertise, data, feedback from experience) and epistemic and aleatory uncertainties.…”
Section: Limits Linked To Implementing Resilience Control Systemsmentioning
confidence: 99%
“…It depicts perfect system resilience with negligible hydrocarbon release, achieving a successful performance of the operation. 5 Shuttle tanker (ST) hose connection 1.1E-01 E 6 Hose aging 1.7E-01 E 7 Joints rupture 4.5E-02 E 8 Valves control system 1.0E-03 E 9 Telemetry system 2.4E-02 E 10 Communication 6.2E-03 E 11 Controllable pitch propeller 1.8E-02 E 12 Zone classification in terms of sensitivity 1.5E-01 E 13 Adequate flow control 1.5E-02 E 14 Level monitoring 1.0E-05 E 15 Oil spillage preparedness program 1.0E-01 E 16 Avoid collision 3.1E-03 E 17 Erroneous operations 3.3E-03 E 18 Corrosion management 3.7E-03 E 19 Secure connection 9.9E-02 E 20 Malfunction of alarm system 9.0E-03 E 21 Hydrocarbon release detection system 2.3E-03 E 22 Tension cause by waves height 4.5E-02 E 23 High wind intensity 1.0E-01 E 24 Low visibility 5.5E-04 E 25 Ice management 1.0E-01 E 26 Emergency shutdown system failure 1.3E-04 E 27 Position reference system 2.0E-03 E 28 Dynamic positioning system 5.0E-04 E 29 Avoid risky maneuvering 7.9E-03 E 30 Vessel motion monitoring 1.0E-01 E 31 Distance keeping 3.8E-02 E 32 Avoid drive-off 5.4E-03 E 33 Early detection 7.2E-05 E 34 Available workforce 1.0E-01 E 35 Reactive maintenance 2.3E-03 E 36 Onsite restoration facility 1.7E-01 E 37 Manning competence 2.7E-01 E 38 Lesson learned 1.0E-01 E 39 Toolkit training 1.6E-03 E 40 Good practice guidance 1.0E-03 E 41 Lack of motivation 1.6E-03 E …”
Section: Baseline Scenariomentioning
confidence: 99%
“…(4) It has been recognized as an important characteristic of maritime operations. (5) Bakkensen et al (6) defined system resilience as the ability of a system to continue its functionality and performance efficiently over the duration of a disruptive event. Guikema et al (7) identified knowledge gaps related to the vulnerabilities, risk, and resilience of modern infrastructure systems that are critical for an improved system performance.…”
Section: Introductionmentioning
confidence: 99%